Windows Network security fundamentals (O'Reilly Media, Inc., 2022)
Many organizations now use a hybrid environment in which existing on-premises networks are supplemented by cloud resources. The challenge is that security in such a world is even more complex than before. Expert Glenn Weadock offers an overview of Microsoft security technologies for today’s hybrid environments. Join in to build a foundation for the security topics you’ll need to pass a number of Microsoft certification exams.